2021
DOI: 10.4103/jfmpc.jfmpc_1871_20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of erectile dysfunction and associated factors among males visiting family medicine clinics in a Tertiary Care Hospital in Karachi, Pakistan

Abstract: Background: The burden of erectile dysfunction (ED) among the developed countries is found to be quite high. However, there is a paucity of data among developing countries to know its actual burden and factors associated with it. Methods: The current study is cross-sectional and was conducted in Family Medicine clinics of Liaquat National Hospital during May 2017–January 2018. A total of 450 males participated in this study with the age range of 24–77 years. More than h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…This showed that ED increases with hypertension. This finding is similar to finding in other studies [15,16].…”
Section: Discussionsupporting
confidence: 93%
“…This showed that ED increases with hypertension. This finding is similar to finding in other studies [15,16].…”
Section: Discussionsupporting
confidence: 93%
“…Recently, around 21% of males have been reported to visit primary health care with complaints of erectile dysfunction (ED). [ 1 ] This figure is similar to one reported by Capogrosso et al . [ 2 ] that every fourth male visiting primary health care is diagnosed with ED.…”
Section: Introductionsupporting
confidence: 91%
“…This finding is in line with research conducted in the Amhara region of Ethiopia 85.5% [ 41 ], in Ghana 81.8% [ 52 ] and Indonesia 84.4% [ 53 ]. Moreover, this study found a higher prevalence compared to researches done in most areas of Ethiopia(54.3-69.9%) [ 19 , 39 , 54 , 55 ], Eritrea 74.2% [ 56 ] ,Tanzania 55.1% [ 50 ], recent systematic review done in Africa 71.45% [ 57 ], Western Asia 62.2% [ 58 ], China 64.2% [ 40 ], South America 74.6% [ 59 ], Bangladesh(45.3-60.2%) [ 35 , 60 ], Sri Lanka 62.9% [ 51 ], Pakistan 21.1% [ 31 ], Nepal 76.8% [ 61 ], India 68.5% [ 27 ] and Europe 67.4% [ 62 ]. This might be due to the study participants characteristics like older age and higher fasting blood sugar.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies have been conducted to determine the magnitude of erectile dysfunction and its determinants [ 26 , 31 36 ]. However, the wide scope of the problem necessitates studying and analyzing the various factors that are potentially associated with erectile dysfunction at once [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%